Symptom science research conducted in community programs funded by the US National Cancer Institute: a 12-year review, 2008 to 2019. - Germain, Diane St.; Stevens, Worta McCaskill; O'Mara, Ann (Supportive Care in Cancer, 2022)
Purpose: This study was conducted to describe the portfolio of symptom science research conducted through the community oncology network supported by the US National Cancer Institute during the 12-year period 2008 to 2019.Methods: The National Cancer Institute conducted a retrospective review of the National Cancer Institute database to identify pediatric and adult symptom management studies that were opened between 2008 and 2019 in the community oncology network and to determine types of studies, accrual patterns, completed studies, and number of publications reporting clinical trial results.Results: The NCI community oncology network conducted 109 symptom studies between 2008 and 2019. The majority of these studies were phase II and III clinical trials. Neurotoxicities were the most frequently occurring symptom studied, with the majority of those focused on neurocognitive impairments. Gastrointestinal symptoms, pain, and fatigue were the next most frequently studied. A variety of interventions were utilized including pharmacologic, behavioral, complementary and alternative medicines, and radiation therapy. Accrual to symptom studies ranged from a low of 896 participants in 2008 to a high of 3468 participants in 2012. The number of open studies ranged from 8 in 2008 to 35 in 2012.Conclusions: Examining the symptom science portfolio of the NCI community oncology network has identified research gaps and has highlighted the need to focus on a mechanistic understanding of symptoms and phenotyping of patients experiencing cancer and treatment-related symptoms. Subsequently, targeted interventions can be developed to prevent or treat these symptoms.